2009
DOI: 10.1103/physrevb.80.214427
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spin transport in graphene field-effect transistors

Abstract: Electronic spin transport in graphene field-effect transistors Popinciuc, M.; Jozsa, C.; Zomer, P. J.; Tombros, N.; Veligura, A.; Jonkman, H. T.; van Wees, B. J. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
279
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(294 citation statements)
references
References 45 publications
14
279
1
Order By: Relevance
“…(1) in the z direction and use the BrataasNazarov-Bauer boundary condition at the NM/FMI interface [5]. From the solution one can obtain an expression for the nonlocal resistance at the FM detector that reads [37,42,43]…”
mentioning
confidence: 99%
“…(1) in the z direction and use the BrataasNazarov-Bauer boundary condition at the NM/FMI interface [5]. From the solution one can obtain an expression for the nonlocal resistance at the FM detector that reads [37,42,43]…”
mentioning
confidence: 99%
“…This makes graphene an indispensable material for the further development of nanoelectronics. Moreover, owing to the large spin-relaxation length, it can be effectively used in spintronics as a material for graphene spin filters and for graphene field-effect transistors [5][6][7][8][9]. However, up to now graphene is used in spintronics only as a passive element due to the low magnitude of the spin-orbit splitting of graphene π states.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating the situation are the many possible sources of spin relaxation in experiments on SiO 2 substrate including charged impurity (CI) scatterers, 16,17 Rashba SO coupling due toadatoms, 18,19,25 ripples, 20,21 and edge effects. 17,23 Early experiments on spin transport in exfoliated graphene were able to take advantage of the tunable carrier concentration (n) and observe a linear relationship between τ s and τ p , thus suggesting EY. 15,22 However, recent theoretical studies have shown that DP is expected to dominate over EY 21,24 and that Elliot's approach applied to graphene 17 predicts τ s = ( F ) 2 τ p /(∆ SO ) 2 , for which both Fermi energy F and τ p depend on carrier concentration, thus highlighting the need for experiments that can tune τ p at fixed n. * roland.kawakami@ucr.edu…”
mentioning
confidence: 99%
“…In graphene, two possible spin relaxation mechanisms are discussed in the literature: [14][15][16][17][18][19][20][21][22][23][24] the Elliot-Yafet (EY) mechanism, for which the spin relaxation time (τ s ) is proportional to the momentum scattering time (τ p ), and the D'yakonov-Perel (DP) mechanism, for which τ s ∝ 1/τ p . Complicating the situation are the many possible sources of spin relaxation in experiments on SiO 2 substrate including charged impurity (CI) scatterers, 16,17 Rashba SO coupling due toadatoms, 18,19,25 ripples, 20,21 and edge effects.…”
mentioning
confidence: 99%